Do you love shrimp? : learn all about them - Rudloe, Jack (FTPress Delivers elements., 2010)
This is the eBook version of the printed book. If the print book includes a CD-ROM, this content is not included within the eBook version. Don't just eat shrimp: discover their amazing story!People love to eat shrimp, fishermen roam the seas catching them, and farmers grow them in ponds-creating a conflict as old as humanity: hunter-gatherers vs. agriculture. Farmers provide so many cheap shrimp that low prices have nearly destroyed the fishermen. All this human activity swirls around small crustaceans with long whiskers, bulbous eyeballs on stalks, ten legs ... If you liked this Element, read more from Jack and Anne Rudloe, including Shrimp: The Endless Quest for Pink Gold (ISBN: 9780137009725). Available in print and digital formats.